Risk disclosures in annual reports and firms’ default risk - Jin, Shunyao; Lee, Hei‐Wai; Xie, Yan Alice (The Journal of corporate accounting & finance, 2024)
This study examines how the length, content, and tone attributes of risk disclosures in a firm's 10‐K annual report relate to its default risk in the subsequent fiscal year. We find a significant association between specific attributes of risk disclosures and the default risk in the subsequent period. Using the 2008 financial crisis as a shock to firms’ risk environment, we further find that the documented association is more pronounced in the post‐financial crisis era. Our cross‐sectional analyses reveal that the documented relationship is particularly prominent for firms undergoing substantial shifts in default risk, facing significant financial distress, operating in industries with lower litigation risk, or subject to heightened scrutiny from external monitors. Overall, our findings suggest that risk disclosures in firms’ annual reports offer valuable insights for investors assessing financial distress and default risk.